Clinical and laboratory factors affecting the prognosis of severe combined immunodeficiency - ÖZTÜRK, ELİF; ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA; AYDINER, ELİF (My University, 2022)
Purpose Severe combined immunodefciency (SCID) is one of the most severe forms of inborn errors of immunity characterized by absence or loss of function in T cells. The long-term outcomes of all forms of SCID have been evaluated in a limited number of studies. We aimed to evaluate the pre- and post-transplant manifestations of SCID patients and determine the factors afecting the survival of patients. Methods We included 54 SCID patients (classical SCID, Omenn syndrome, atypical SCID (AS)) in this study. We evaluated the clinical presentation, infections, and outcome of hematopoietic stem cell transplantation (HSCT). Lymphocyte subsets and T-cell receptor (TCR) repertoire were analyzed by fow cytometry. Results The median age at diagnosis was 5 (range: 3–24) months and follow-up time was 25 (range: 5–61) months. Symptom onset and diagnostic ages were signifcantly higher in AS compared to others (p = 0.001; p < 0.001). The most common SCID phenotype was T-B-NK +, and mutations in recombination-activating genes (RAG1/2) were the prominent genetic defect among patients. The overall survival (OS) rate was 83.3% after HSCT, higher than in nontransplanted patients (p =0.001). Peripheral blood stem cell sources and genotypes other than RAG had a signifcant favorable impact on CD4+ T cells immune reconstitution after transplantation (p=0.044, p=0.035; respectively). Gender matching transplantations from human leukocyte antigen (HLA)–identical and non-identical donors and using peripheral blood stem cell source yielded higher B-cell reconstitution (p=0.002, p=0.028; respectively). Furthermore, receiving a conditioning regimen provided better B-cell reconstitution and chimerism (p = 0.003, p = 0.001). Post-transplant TCR diversity was sufcient in the patients and showed an equal distribution pattern as healthy controls. The OS rate was lower in patients who underwent transplant with active infection or received stem cells from mismatched donors (p=0.030, p=0.015; respectively). Conclusion This study identifes diagnostic and therapeutic approaches predictive of favorable outcomes for patients with SCID.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); IMMUNOLOGY; Life Sciences (LIFE); Genel İmmünoloji ve Mikrobiyoloji; Immunology; General Immunology and Microbiology; Severe combined immunodeficiency; Bone marrow transplantation; Immune reconstitution; T-cell receptor repertoire; Prognosis; STEM-CELL TRANSPLANTATION; IMMUNE RECONSTITUTION; BONE-MARROW; CHILDREN; SURVIVAL; OUTCOMES; Severe combined immunodefciency; Bone marrow transplantation; Immune reconstitution; T-cell receptor repertoire; Prognosis